Fiqh Classification and the Methodology for Determining the Legal Ruling of the Indonesian Ulema Council's Fatwa on Intellectual Property Rights - Panji Adam Agus Putra; Ira Siti Rohmah Maulida; Nazwa Divalya Raya Gunadi (Fakulti Ekonomi dan Muamalat, 2025)
International Islamic Economic System Conference (I-iECONS 2025) "Digitalization, Innovation and Sustainable Development Through Islamic Economics"/ editors: Amalina Mursidi & Nur I'ffah Muhammad Nasir Organized by the Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia (USIM) Conference Dates: 26-31 August 2025